Mentoring in a Catholic High School: The Movement to Receive - Pang, Alfred KM (Lumen et Vita, 2012)
This paper explores the dynamics that underlie the process of mentoring high-school students, with Catholic Junior College in Singapore as a site of practice. Using Luke’s journey narrative of Jesus’ walk with the two disciples to Emmaus (Luke 24:13-35), it proposes a Christological framework that construes the relational practice of mentoring as involving four movements - receiving, blessing, breaking and giving. Within the limited scope of this paper, I focus specifically on the movement of receiving: What does it mean to receive a young person as a mentee? In what manner can a teacher-mentor receive the young person? What practical strategies can teacher-mentors employ to help them ‘see’ where the young person is at?